Biogeographic vulnerability to ocean acidification and warming in a marine bivalve. (January 2018) - Van Colen, Carl; Jansson, Anna; Saunier, Alice; Lacoue-Labathe, Thomas; Vincx, Magda
Abstract: Anthropogenic CO2 emissions are rapidly changing seawater temperature, pH and carbonate chemistry. This study compares the embryonic development under high pCO2 conditions across the south-north distribution range of the marine clam Limecola balthica in NW Europe. The combined effects of elevated temperature and reduced pH on hatching success and size varied strongly between the three studied populations, with the Gulf of Finland population appearing most endangered under the conditions predicted to occur by 2100. These results demonstrate that the assessment of marine faunal population persistence to future climatic conditions needs to consider the interactive effects of co-occurring physico-chemical alterations in seawater within the local context that determines population fitness, adaptation potential and the system resilience to environmental change. Highlights: Low pH reduces hatching in the Baltic, southern and northern East Atlantic clade. Temperature rise alleviates pH effects on hatching success in the East Atlantic clades. Smallest hatching sizes were found in low pH (< 7.5) calcite-undersaturated seawater. Temperature rise reduces hatching size in the Baltic and northern East Atlantic clade. The Gulf of Finland population appears most endangered in future high pCO2 waters.